Tummy time to improve psychomotor development Babies 6-9 months - Luluk Yuliati; Risnawati Sabang (Institute of Computer Science (IOCS), 2023)
The practice of tummy time has been included in various guidelines for baby care but is still not widely known by Indonesian people. The purpose of this study was to determine the effect of giving tummy time on the psychomotor development of infants aged 6-9 months in the Working Area of the Membey Health Center. The research utilized a pre-experimental design known as the one-group pretest-posttest design. The population of this study was all infants aged 6-9 months, with a purposive sampling technique and a sample size of 32 respondents. Measurement of motor development was carried out using developmental pre-screening questionnaires, while tummy time was recorded in diaries, observation sheets, and interviews. The results of the research data were tested using the analysis Wilcoxon Signed Ranks Test. Most of the psychomotor development before giving tummy time in infants aged 6-9 months was found to be more doubtful (78.1%), after giving tummy time the results increased to conform with several of 20 respondents (62.5%). Tummy time has been shown to affect increasing psychomotor development in infants aged 6-9 months with a Z count of -4.231 with a p-value = <0.0001. Tummy time promotes motor development and offers practical recommendations.